EFFECTIVENESS OF CYCLOSPORINE IN SYSTEMIC TYPE OF JUVENILE IDIOPATHIC ARTHRITIS - V.A. Kel'tsev; L.I. Grebenkina ("Paediatrician" Publishers LLC, 2010)
This is a case report of severe juvenile idiopathic arthritis in child, conditioned as by main disease as by inadequate hormonal treatment. Therapy with cyclosporine furthered development of clinical and laboratory remission of disease, inhibition of process of anatomical destruction and activation of reparation of femoral head, bone tissue in acetobular region of iliac and sciatic bones. Key words: juvenile idiopathic arthritis, cyclosporine, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):147-150)